NGO workers' internalisation of the human rights-based approach in Bangladesh. Issue 4 (18th May 2016) - Noh, Jae-Eun
ABSTRACT: The Western origin of human rights raises the question of how the human rights-based approach to development (HRBA) is understood in non-Western countries. This article explores individual practitioners' perceptions of the HRBA in an NGO working in Bangladesh, drawing on interviews with its workers. The data suggest that participants accept the universal values of human rights and make sense of the HRBA influenced by their organisational and national contexts. Conceptualising this process as "internalisation", this article argues that the organisational support and workers' field experience are critical for incorporating contextual consideration into their interpretation and practice of the HRBA.